Comparative Analysis of the Microbial Profiles in Supragingival Plaque Samples Obtained From Twins With Discordant Caries Phenotypes and Their Mothers - Zheng, Yuqiao; Zhang, Meng; Li, Jin; Li, Yuhong; Teng, Fei; Jiang, Han; Du, Minquan (Frontiers in Cellular and Infection Microbiology, 2018)
Early childhood caries(ECC), the most frequent disease of oral cavity in preschool children, is the consequence of microbial, genetic, biochemical, socioeconomic, physical, environmental, and health-influencing behavioral factors. To investigate the role of the oral microbiome and the impact of host and environmental factors in the occurrence and development of ECC, we studied the supragingival plaques of 14 twin pairs and a set of triplets with discordant caries phenotypes and of 15 mothers, applying the HOMINGS (Human Oral Microbe Identification using Next Generation Sequencing) technique. A total of 2,293,650 reads revealed 11 phyla,116genera and 139 species of micro flora. Comparative analysis between the caries group and the caries-free group at species level revealed that the abundance of Streptococcus mutans, Lactobacillus fermentum, Actinomyces islaelii, Neisseria sica and Veilonella dispar exhibited much higher in caries group (P<0.05). Furthermore, monozygotic twins exhibited a higher degree of similarity than dizygotic twins. At last, we analyzed the relationship of environmental factors and oral microbiome, and results indicated that the frequency of taking sweet food was associated with ECC. Conclusions: First, Streptococcus mutans, Lactobacillus fermentum, Actinomyces israelii, Neisseria sica and Veilonella dispar are strongly associated with ECC and can serve as potential biomarkers of dental caries during the primary dentition. Second, genetic components influence the oral microbiome composition, while environmental and behavioral factors like the frequency of taking sweet foods have an impact on the distribution of caries related bacteria.